Building and standardizing skill tests based on visual scanning for players in the Iraqi Star League clubs - Ahmed, saif; Finjan, Faleh (Journal of Physical Education, 2024)
To the research and its importance: Tests are considered as a contributing tool for evaluation in the sports field, on which the rest of the sciences are based, the most important of which are learning and training or evaluating the level of performance and revealing errors in competition conditions and working to develop them objectively and accurately. Sight is one of the most important sources of receiving information that serves all the functions of the body by identifying the external environment and giving us information about everything that is happening around us from movements or moving objects or objects passing in front of us or the flight of balls and their speed and approach, and the individual can also determine the locations of things and their position from him, whether in terms of their proximity or distance from him, as studies and research have proven that visual training has a direct impact on the accuracy of players’ performance and the speed of motor response to technical skills. Skill performance includes a motor aspect and a visual aspect. If the visual aspect does not work efficiently, this will naturally affect the accuracy and speed of motor response to skill performance. It must be noted that many visual training exercises are linked to different aspects of the game of football, including the skill aspect. Therefore, we find that all skill requirements need a deep vision and correct reading of how to employ these requirements in order to reach the appropriate space in which the player moves freely and easily, away from obstructing competitors. A good and comprehensive visual vision of the field’s surroundings prepares and employs the appropriate spaces from which the player can perform the appropriate skills that help in moving in these spaces freely with a slight obstruction until the offensive movement is executed well. Some studies confirm that the best and most aware players are those who look at the game and do not follow or look at the ball only, as elite players always direct their face and eyes towards the players’ movement quickly and continuously, and within ten seconds it reaches 7 or 10 times, so researchers and coaches must find tests similar to playing and competition situations, so the researcher resorted to designing skill tests according to the visual scanning of football players that are similar to playing during the match, and from here the importance of the study is evident in developing skill tests using the visual scanning of the field’s surroundings and performing the skill during movement.